Social Media Activity And Trust In Digital Vs. Traditional News: A Quantitative Analysis - Nunik Hariyani; Jayadi Jayadi; Azizah Choirunisa Azzahra (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to analyze the relationship between social media activity and the level of trust in digital news, both disseminated through social media and traditional media. With a quantitative approach and explanatory design, data were collected through a survey of 300 social media active respondents in Indonesia and analyzed using the Pearson correlation test and simple linear regression. Results showed a positive and significant relationship between social media activity and trust in news on social media (r = 0.478; β = 0.472; R² = 0.229), but there was no significant association with trust in news in traditional media (r = –0.108; β = –0.094; R² = 0.011). These findings suggest that nearly a quarter of the variation in trust in digital news can be explained by the intensity of users' social activity in digital media, with trust mechanisms driven more by algorithmic exposure, social validation, and echo chamber effects than institutional credibility. This study confirms and contextualizes the media trust model and agenda-setting theory in Indonesia's digital environment, especially considering that 91% of respondents stated that they first encountered news through social media. This study recommends strengthening digital literacy based on social interaction and developing news distribution strategies adaptive to people's digital trust patterns.